2011
DOI: 10.1111/j.1463-1326.2010.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin on cardiovascular events and mortality: a meta-analysis of randomized clinical trials

Abstract: Available evidence seems to exclude any overall harmful effect of metformin on cardiovascular risk, suggesting a possible benefit versus placebo/no treatment. The observed detrimental effect of the combination with sulphonylureas deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
200
0
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(233 citation statements)
references
References 28 publications
8
200
0
18
Order By: Relevance
“…101 Further information on the cardiovascular safety and efficacy of linagliptin versus glimepiride will be provided by the ongoing prospective CAROLINA ("CARdiovascular Outcome study of LINAagliptin versus glimepiride in patients with T2DM") study in which numerous patients will receive metformin as baseline therapy 102 . Meta-analyses reported that both metformin 103 and linagliptin 104 may be associated with a reduced incidence of cardiovascular events, suggesting that combination of the two drugs may be of potential interest in T2DM patients at high cardiovascular risk.…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“…101 Further information on the cardiovascular safety and efficacy of linagliptin versus glimepiride will be provided by the ongoing prospective CAROLINA ("CARdiovascular Outcome study of LINAagliptin versus glimepiride in patients with T2DM") study in which numerous patients will receive metformin as baseline therapy 102 . Meta-analyses reported that both metformin 103 and linagliptin 104 may be associated with a reduced incidence of cardiovascular events, suggesting that combination of the two drugs may be of potential interest in T2DM patients at high cardiovascular risk.…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“…54,55 It is generally considered weight-neutral with chronic use and does not increase the risk of hypoglycemia. Metformin is associated with initial gastrointestinal side effects, and caution is advised to avoid its use in patients at risk for lactic acidosis (e.g., in advanced renal insufficiency, alcoholism), a rare complication of therapy.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Les résultats varient selon les méta-analyses considérées, avec une réduction de la mortalité CV dans une première méta-analyse publiée [25], mais pas vraiment confirmée dans deux autres [13,26] …”
Section: Méta-analysesunclassified
“…• Les différentes méta-analyses disponibles donnent des résultats disparates, liés aux types d'essais retenus et au comparateur pris en compte, notamment [13,[25][26][27]. Quoi qu'il en soit, elles n'ont pas réussi à démontrer, de façon évidente, un effet protecteur de la metformine.…”
Section: Metformineunclassified